(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article considers national-cultural peculiarities of English and Ukrainian grammar. It states that selection of grammar material is influential in foreign language study due to the fact that it identifies students’ readiness to spontaneous communicative situations, spurs to modeling their own ones. The paper points out to a fact that there is a robust relationship between cultural values and grammar as exemplified by the contrast of word order, use of the imperative mood and tense forms in grammar of the English and Ukrainian languages. Thorough analysis demonstrates that the Ukrainians have an inherent feature of moderate distance and frankness in communication; are easy to get in touch with strangers. Such cultural characteristics are echoed in flexible word order in the Ukrainian language. Englishmen are inclined to well-advised actions; their relations are more distant and shallow, which is confirmed by restrictive word order. The article focuses on distinction between the application of the imperative in English and Ukrainian. The research suggests that in Ukrainian the use of the imperative doesn’t level down politeness. Insistent appeal to a conversation partner warns against unwanted actions and is considered to be a display of respect. Therefore, categorical imperative is expressed by infinitive in negative form that suggests action tendency or command. Representatives of foggy Albion use the imperative limitedly to avoid direct impact on a speaker. They abstain from dogmatic judgments, conceal their openness and straightforwardness. In accordance with this categorical imperative is formed by means of the gerund or infinitive with polite formulae, so that the phrase is perceived as advice, request or gratitude. The paper examines the category of time which differs in systems of English and Ukrainian. It reveals that time interval is inessential for Ukrainians. Thereunder, there are four tense forms in Ukrainian grammar. The extensive system of tense forms in English, which amounts to 12, indicates that representatives of English speaking society divide time into periods, that promotes successful accomplishing of primary and secondary tasks.